Growth is not over for Starbucks,it is empowered by digital and geographic expansion - Oliveira, Sofia Isabel Simões De (2020)
This paper is an equity research on Starbucks Corporation. During this report, it will be analyzed the current status of the coffee retailing industry, how it is going to evolve in the future and how it will influence Starbucks’ value creation. Moreover, Starbucks’ main revenue drivers will be studied and projected until 2031, based on the company strategy and on the overall external conditions affecting its activity. The result is the company’s cash-flows until 2031, which will be used to compute the valuation of the company in 2020,using the fundamental analysis, predicting Starbucks’ share price in this year. Lastly, it will be computed the return that shareholders should expect, in order to release our final recommendation, which is to buy the stock.